Shea butter republic : state power, global markets, and the making of an indigenous commodity - Chalfin, Brenda (Routledge, 2004)
This ethnographic study traces shea from a pre- to post-industrial commodity to provide a deeper understanding of emerging trends in tropical commoditization, cosmopolitan consumption, global economic restructuring and rural livelihoods.